Influence of renewable energy and natural resources on climate change: The role of green innovation in China - Jiang, Dayang; Shu, Hansong; Fan, Yifan; Dong, Yuting; Li, Haiwei (Frontiers in Environmental Science, 2022)
The economic progress of China cannot be denied; however, detoriating enviornmental quality is the primary concern to be addressed. Since last few years, China’s legislators are intending to facilitate green transformation by sustaining natural resources and ensuring renewable energy consumption. Therfore, this study explores the impact of renewable energy, natural resource green innovation and economic growth on ecological footprints in China. To achieve the objectives, bootstrap Autoregressive distributed lag (ARDL) model has deployed by taking the quarterly data ranging between 1990Q1 to 2020Q4. The results reveal that by enhancing green innovation, China can transform their economy towards a clean environment. Similarly the effective utilization of renewable energy consumption is indispensable to reducing the ecological footprint in the long run. Moreover, the Errror Correction Term (ECT) is significantly negative, confirming a stable long-run equilibrium relationship between model variables. A similar results are found in the short-run, however, the marginal impact of all variables are stronger in long-run. It implies that for optimal benefits from renewable energy and gren technologies, a long-term planning is imperativce in China.